Mid-season lodging modulates photosynthesis, evapotranspiration, and dry matter accumulation and distribution simulated by the optimized model in maize - Peng, Jiyong; Lu, Liang; Noor, Mehmood Ali; Li, Shuyan; Ma, Wei; Wang, Jing (Frontiers in Ecology and Evolution, 2023)
We examined the effects of lodging on photosynthesis, dry matter accumulation, and distribution of maize in Zhengzhou Agro-meteorological station in 2016, following a strong wind lodging process. On the basis of observational data of crops, meteorology, and CO2/H2O flux from milk maturity to maturity of maize in a normal growth year (2017), a model of population photosynthesis and evapotranspiration of maize under normal growth conditions was constructed. As a result of using the validated model to simulate the theoretical value of photosynthesis and evapotranspiration in lodging years (2016), the measured value of population photosynthesis after lodging was calculated based on the measured data of CO2/H2O flux from milk maturity to maturity, and the difference between the simulated value and the measured value of population photosynthesis and evapotranspiration in lodging years (2016) was compared and analyzed. The correlation between dry matter accumulation and population photosynthetic accumulation was examined in order to estimate the reduction of dry matter accumulation after lodging. The effect of lodging on dry matter accumulation, distribution, and yield were analyzed using field biomass data. The population photosynthesis model could accurately simulate the characteristics of population photosynthesis rate under normal growth conditions of maize, and the absolute error between the simulated value and the measured values in 2017 was -0.43 mg·m-2·s-1, and the relative error was -3.3%. In 2016, the measured value of photosynthesis after lodging was significantly lower than the simulated value, and the daily average population photosynthesis rate decreased by 13.99 mg·m-2·s-1, or 53%. The lodging process altered the accumulation and distribution of dry matter in maize. The dry weight of stem and sheath increased by 5.5% and ear weight decreased by 10.9% after lodging compared with that without lodging, but had no significant effect on leaf dry weight. After lodging, the proportion of stem sheath distribution increased by 3.0%, while the proportion of ear distribution decreased by 3.0%. After lodging, 100 grain weight and plant grain weight decreased by 2.8% and 10.8%, respectively. According to the theoretical yield calculated based on the lodging rate and density, the yield of the entire field was reduced by 5.0%.